Examining the Future Trajectory of Entrepreneurship. (21st September 2017) - Kuratko, Donald F.; Morris, Michael H.
Abstract : Consistent with the theme of this special issue, entrepreneurship today is truly everywhere—across campuses, across communities, and across borders. However, we know that entrepreneurship is being defined in different ways … by different audiences! Exactly how entrepreneurship gets redefined and by whom is the major challenge confronting the discipline as that will forge the future trajectory for everyone. In order to avoid the tendencies to apply entrepreneurship in virtually any context no matter how far removed it is from the act of recognizing and capitalizing on opportunity for the purposes of economic or social gain, this paper examines six major trajectories that will significantly influence the future of this discipline.